Shooter ready? Integrating mental skills training in an advanced sniper course - Ytterbøl, Christian; Collins, Dave; MacPherson, Alan (Frontiers in Psychology, 2023)
Performance psychology has increased in usage and popularity; however, we contend that within the elite spheres of the military there is a need for research and development to fit the context and environment. In this paper we describe an explorative case study on the integration of mental skills training techniques to an advanced sniper course in the Norwegian Armed Forces. We evaluate the impact through triangulation, examine results on the course, perceptions of the participants and observations from the instructors. In addition, we conducted a one year follow up to get participants’ experience of translating the skills beyond the course. Results show that the mental skills training package influenced both results and performance in a positive manner, however as a novel field, further research is warranted to establish a best practice to enhance performance for elite military forces.